Major problems of air traffic are inclusion of aviation in the european union carbon emission trading scheme and noise protection - Đurđev, Dušanka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In 2008, aviation activity was included in the European Union Emissions Trading Scheme (EU ETS), imposing legal obligations on all airlines around the world, not just those in the European Union. Considering this scenario, the aim of the article is to reflect on the admissibility of the unilateral imposition of obligations justified by environmental concerns. Aircraft noise has been a sensitive issue for residents in areas near airports since jet aircraft became widely used in the 1960s and 1970s. This has led governments and industry to seek constant improvement in the level of noise generated by individual aircraft, notably by reaching agreement at global level (ICAO) on the introduction of increasingly stringent standards